Demographic Determinants of Fear of Success Among Married Female Civil Servants: Evidence from the Directorate General of Taxes - Debora Novryati Laise; Nilam Widyarini (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
Fear of success (FoS) can significantly impede career advancement when anticipated social sanctions, role conflicts, or workload spillovers make professional achievement feel psychologically and socially costly. This phenomenon may be particularly pronounced among married female civil servants who face strong traditional role expectations in Indonesia's collectivist society. Objective: To examine how demographic characteristics (age, work tenure, education, number of children, position level, and spouse employment) systematically relate to fear of success among married female civil servants in Indonesia's Directorate General of Taxes. Methods: A cross-sectional survey design was employed with 205 married female civil servants. Fear of Success was measured using the validated Zuckerman & Allison (1976) scale with 16 retained items (5-point Likert scale). Statistical analyses included ANOVA/MANOVA, hierarchical multiple regression, and comprehensive robustness checks. Results: Fear of success varied significantly by age (F=3.45, p=0.009) and tenure (F=2.89, p=0.023), with peak levels occurring at mid-career stages (ages 41-46 years; 16-20 years tenure). Number of children positively predicted FoS (β=0.156, p=0.022), while education level differences were non-significant (p=0.072). The demographic model explained 16% of variance in fear of success. Conclusions: Demographic patterns particularly mid-career timing—highlight critical windows for targeted, family-aware career development interventions. These findings have important implications for gender-sensitive talent management in bureaucratic settings and contribute to understanding psychological barriers to women's career advancement in developing countries.